Pengaruh Model Pembelajaran Blended Learning Berbasis Media Website terhadap Pemahaman Konsep Mata Pelajaran Siklus Akuntansi di Sekolah Menengah Kejuruan - Gilang Asoka Ramadhan; Andri Eko Prabowo (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study addresses the low conceptual understanding of students in the accounting cycle subject at SMK PGRI Pekanbaru, which has been dominated by direct learning methods. The main purpose is to examine the effect of implementing a website-based blended learning model on students’ conceptual understanding of the accounting cycle. This research is relevant to the ongoing educational transformation toward technology-integrated and student-centered learning in vocational schools. The study employed a quantitative approach using a pre-experimental design (one group pretest–posttest design). The research subjects were 21 tenth-grade Accounting and Finance (AKL) students. Data were collected using a validated and reliable multiple-choice test instrument that measured students’ conceptual understanding. The data were analyzed using a paired sample t-test with SPSS version 25 to determine significant differences between pretest and posttest scores. The results revealed a significant increase in students’ conceptual understanding after the implementation of the website-based blended learning model. The mean pretest score was 69.04, which was below the school’s Minimum Completion Criteria (KKM). The posttest results showed a statistically significant improvement, indicating that the blended learning model effectively enhanced students’ conceptual mastery. This study highlights the potential of website-based blended learning to improve conceptual understanding and student engagement. However, the research was limited to a small sample in one school, which restricts the generalizability of the findings. Future research should involve larger samples and compare multiple blended learning platforms.